Auditor Style Dan Komparabilitas Laporan Keuangan - Riski Wulandari; Henri Agustin; Mayar Afriyenti (Universitas Negeri Padang, 2019)
Auditor style defined as a unique set of internal working rules for the interpretation and enforcement of accounting standard within the auditor’s clienteles belongs to particular audit firm, especially Big 4 audit firms. As a consequence, financial statements of two companies audited by the same Big 4 auditor, subjected to the same audit style, tend to have comparable earnings which have a more similar accrual, than two companies audited by two different Big 4 auditors with different styles. This research attempts to examine the effect of this auditor style issue on manufacturing financial statement comparability listed in Indonesian Stock Exchange. For five years’ observations, through 2012-2016 this research demonstrated a result with auditor style affects the comparability of reported earnings within a Big 4 auditor’s clientele and found no effect of auditor style on financial statement comparability within a non-Big 4 auditor’s clientele